The ichnology of carbonate drifts. Issue 4 (18th February 2019) - Reolid, Jesús; Betzler, Christian
Abstract: Carbonate drifts have so far not been as intensely investigated as their siliciclastic equivalents, especially from an ichnological perspective. The aim of this work is therefore to provide an overview of the different bioturbation styles in carbonate drifts for ichnologists and sedimentologists working in such deposits. Different types of carbonate drifts from the Maldives were studied to address this objective. The cores recovered during International Ocean Discovery Program Expedition 359 were examined to provide the sedimentological and ichnological data for a detailed analysis of the ichnology of carbonate drifts. The ichnological characteristics of the Maldives drifts are compared to other carbonate drifts in order to discuss similarities and differences, and thus provide an overview of the general characteristics of carbonate drift ichnology. These drifts are located in the Santaren Channel which lines Great Bahama Bank, along the Marion Plateau in Australia, in the Limassol and Larnaca basins in Cyprus and in the Danish Basin in Denmark. The common characteristics of bioturbation in carbonate drifts are: (i) the complete bioturbation of the sediment with bioturbation indexes between four and six; (ii) the occurrence of distinctive trace fossils limited to facies contacts or condensed intervals; (iii) a typical ichnoassemblage consisting of Thalassinoides, Scolicia, Planolites, Zoophycos, Chondrites, Phycosiphon and Palaeophycus; (iv) the contiguous occurrence of ichnogenera from different tiers, with only Zoophycos and Chondrites as deep tiers; and (v) distinct infills of the traces including particulate organic matter, pyrite, silica and celestine. In addition, the main ichnofacies of carbonate drifts is the Zoophycos ichnofacies. Ichnofabrics grade from coarse‐grained and completely bioturbated to ichnofabrics with present to rare trace fossils and preserved sedimentary structures. The type and intensity of the bioturbation is controlled by the amount of organic matter and the oxygenation at the sea floor that is determined by the action of bottom currents and the sea‐level fluctuations affecting the carbonate factory in carbonate platforms bordering the basins where the carbonate drifts form. The study of the bioturbation in core and outcrop provides palaeoenvironmental information about carbonate‐drift deposits that complement the classical sedimentological data.